Philologie ou linguistique ? Réponses transcontinentales - Ku-Ming (Kevin) Chang (Revue d’Histoire des Sciences Humaines)
The Chinese and English names of Academia Sinica’s Institute of History and Philology present a puzzle. The Chinese, 歷史語言研究所, suggests that it is an institute of history and linguistics (or language studies). The English name indicates that the institute studies history and philology. For today’s public, linguistics and philology are two different disciplines. Did the founders of the institute confuse the two disciplines? Or how could they equate linguistics with philology at the time? This study suggests that the solution to the puzzle lies in understanding the training of two founding members of the institute, Ssu-nien Fu (or FU Sinian) and Yuen Ren Chao (or ZHAO Yuanren). Fu, trained in Germany, wanted to replicate the achievements of German philological scholarship in his new institute. He followed the German academic mainstream to see language studies as a branch of philology. Invited to head the language section of the institute, Chao received his training in language studies in the United States, France, and England, and joined an Anglo-French movement that began to see language studies as a discipline—linguistics, that is—independent of philology.